The Importance of Coaches’ Autonomy Support in the Leisure Experience and Well-Being of Young Footballers - Balaguer, Isabel; Castillo, Isabel; Cuevas, Ricardo; Atienza, Francisco (Frontiers in Psychology, 2018)
Drawing on the self-determination framework, the study examined the effect of coaches’ autonomy support on the leisure experience of young male football players. Specifically, a model was tested analyzing the long-term predictive power of the players’ perception of coach-autonomy support at the beginning of the season on the subjective vitality of young football players at the end of the season through needs satisfaction and intrinsic motivation. Moreover, we tested whether the effects of coach-autonomy support on the aforementioned variables (needs satisfaction, intrinsic motivation, and subjective vitality) at the end of the season remained at the beginning of the following season. Because the coach in the second season was not the same one as in the first season, the perception of coach-autonomy support at the beginning of the second season was used as a control variable. Three hundred and sixty football players (M age = 12.60 years; SD = 0.52) completed a questionnaire on the variables of interest at the beginning of the first season (T1), at the end of the first season (T2), and at the beginning of the second season (T3). The results of the path analyses showed that player’ perceptions of coach autonomy support at the beginning of the season (T1) positively predicted needs satisfaction at the end of the first season (T2), which in turn predicted intrinsic motivation at the end of the first season (T2). Additionally, intrinsic motivation significantly and positively predicted subjective vitality at the end of the first season (T2). Finally, needs satisfaction, intrinsic motivation, and subjective vitality at the end of the second season (T2) positively predicted these same variables at the beginning of the second season (T3). Results emphasized the importance of the autonomy support offered by the coach in promoting the quality of young people’s leisure experience playing football and its benefits for their well-being.